Repurposing Typical Institutional Hall As Temporary Covid-19 Quarantine Stations In Johor: A Review Study In KKTM - Hanapi, Nur Amalina; Hanapi, Nur Atikah (International Journal of Integrated Engineering, 2021)
The current situation of the world with the pandemic of COVID 19 has brought a mass conversion of places as a temporary shelter recently. In Malaysia, the list of gazetted sites by the government for the COVID quarantine stations were being retrieved in March 2020 to facilitate Ministry of Health in coping with the sporadic diseases. To achieve lower production cost and rapid execution of disaster shelter for the pandemic, possible open plan spaces in institutional building will be identified to perform temporary medical shelter. Resuscitation area, wards, pharmacy, x-ray room, staff room and meeting rooms are among the required spaces in determining the medical layout planning of the particular quarantine station. A descriptive and qualitative design was being used based on the literature review and case studies in order to get the information and to identify clear demarcation of circulation and movement in the quarantine station. Ultimately, foreseeing holistic changes and novel solutions in construction industry in Malaysia, this result will contribute to further assist authorities to gazette other institutional hall as transitional stay which will be become the norms nowadays.